Genomic Feature Analysis of Betacoronavirus Provides Insights Into SARS and COVID-19 Pandemics - Li, Xin; Chang, Jia; Chen, Shunmei; Wang, Liangge; Yau, Tung On; Zhao, Qiang; Hong, Zhangyong; Ruan, Jishou; Duan, Guangyou; Gao, Shan (Frontiers in Microbiology, 2021)
In December 2019, the world awoke to a new zoonotic strain of coronavirus named severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2). In the present study, we identified key recombination regions and mutation sites cross the SARS-CoV-2, SARS-CoV and SARS-like CoV clusters of betacoronavirus subgroup B, and classified two recently detected betacoronavirus strains RmYN01 and RmYN02 (from a bat) belonging to the SARS-CoV and SARS-CoV-2 clusters, respectively. In addition, we reported—for the first time—a recombination event of ORF8 at the whole-gene level in a bat and ultimately determined that ORF8 enhances viral replication. In conjunction with our previous discoveries, we found that the receptor binding ability, junction furin cleavage sites (FCSs), strong first ribosome binding sites (RBSs) and enhanced ORF8s are main factors that account for the extraordinary transmission, virulence and host adaptability of betacoronavirus subgroup B. The strong recombination ability of CoVs integrated these factors to generate multiple recombinant strains, two of which evolved into SARS-CoV and SARS-CoV-2, resulting in the SARS and COVID-19 pandemics. As the most important genomic features of SARS-CoV-2 and SARS-CoV, a novel junction FCS and an enhanced ORF8, respectively, were identified to provide clues for the future study of their origin and evolution.